Perancangan rak penyimpanan untuk mengurangi jumlah produk cacat - Albertus Anggito Pramudito; Yosef Daryanto (Universitas Atma Jaya Yogyakarta, 2023)
Tulakir Fiberglass is a company that produces souvenir items, specifically miniatures made from fiberglass. The company has been experiencing issues with defective products in its warehouse, such as broken items, bulging defects, and damage caused by termites. The company wants a solution to reduce the number of defective products to a maximum of one per month for each product type. We first identified the main cause of the defects, which was found to be poor storage shelves. Therefore, a redesign of the shelves was necessary. The design of storage shelves was carried out using rational methods, which resulted in the creation of new storage shelves made of iron, multiplex, and lining materials, with flexible stack dividers. In addition, we designed a step ladder to help in placing and picking up products from the shelves. Based on the results of implementing the new storage shelves within one month, there were no defective products found among the rows of storage shelves.